Intelligence Education for National Security and Public Safety Policy: A Comparative Analysis of Nigeria, South Africa, and Indonesia (Lex Scientia Law Review, 2022)
National security and public safet policy have become one of the important issues around the world. In some cases, the national security very close to how the State provides various instruments in maintaining national stability, including policies and laws. Nigeria, South Africa, and Indonesia are facing various challenges of national stability including various national security threats. For Nigeria, post-colonial hangs over and extended militarism created huge challenges for the democratisation of intelligence education and training, while in South Africa, centuries of repressive apartheid regime created institutional obstacles for a virile democratic intelligence education and training. This work therefore is a comparative analysis of intelligence education and training in Africa-Nigeria, South Africa, and Indonesia. Using a historiographic and content evaluative methods, the study was able to establish similar developmental trajectory of intelligence education and training in Nigeria, South Africa, and Indonesia and recommended the urgent need for extensive collaboration between the countries to develop a model of intelligence education and training to attenuate the pervasive national security and public safety threats challenges in the countries.